Mucosal melanoma – diagnostic challenge - Karp, Paulina; Lewkowicz, Natalia; Żebrowska, Agnieszka (Dermatology Review/Przegląd Dermatologiczny, 2024)
Mucosal melanoma malignum (mMM) is a rare and aggressive malignancy that carries a poor prognosis. Most commonly, it develops on the mucous membranes in the head and neck region, and within the genitalia. Because of its anatomical location and absence of early symptoms, diagnosing mucosal melanoma malignum presents significant challenges. Consequently, the disease is usually diagnosed at an advanced stage. Dermoscopy is a helpful tool in the early diagnosis of mucosal melanoma malignum. Risk factors for mucosal melanoma malignum are poorly understood so far, but exposure to ultraviolet light is not known to increase the risk of developing the disease. The overall 5-year survival rate for mucosal melanoma ranges from 0% to 45%, with an average survival of 2 years. Early detection is crucial for favourable prognosis.